Association between duration of hypertension, duration of antihypertensive therapy, and medication adherence among patients in a primary care setting in Kendari, Indonesia - La Ode Alifariki; Aning Subiyatin; Dewi Nopiska Lilis (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Background: Hypertension is a chronic non-communicable disease that requires long-term therapy and consistent medication adherence to prevent complications. However, adherence to antihypertensive medication remains low and may be influenced by factors such as duration of hypertension and duration of medication use. Purpose: This study aimed to determine the relationship between duration of hypertension and duration of antihypertensive medication use with medication adherence among hypertensive patients at Abeli Public Health Center, Kendari City. Method: This study employed an analytic observational design with a cross-sectional approach. A total of 62 respondents were selected using purposive sampling. Data were collected through interviews using structured questionnaires, and medication adherence was assessed using the Morisky Medication Adherence Scale (MMAS). Data were analyzed using the Chi-Square test with a significance level of α = 0.05. Results: The analysis showed a significant relationship between duration of antihypertensive medication use and medication adherence (p = 0.007). Respondents with a duration of medication use of 2–4 years had the highest proportion of non-adherence (95.5%). Meanwhile, duration of hypertension was not significantly associated with medication adherence (p = 0.356). Conclusion: Duration of antihypertensive medication use was significantly associated with medication adherence, whereas duration of hypertension was not associated with medication adherence among hypertensive patients at Abeli Public Health Center, Kendari City.